Preliminary distribution of Ephemeroptera, Plecoptera and Trichoptera (EPT) in Kerian River Basin, Perak, Malaysia - Md. Rawi, Che Salmah; Z. S., Amelia; Ahmad, Abu Hassan (Universiti Putra Malaysia Press, 2001)
A preliminary study on three aquatic insect orders, Ephemeroptera (mayfly), Plecoptera (stonefly) and Trichoptera (caddisJly) (EPT) was carried out in Kerian River Basin (KRB), at the border of Kedah-Perak states, in Peninsular Malaysia. Ephemeroptera comprising six families of 10 genera and 460 individuals was the most dominant order. Although both Plecoptera and Trichoptera was represented l7y similar number of families, stoneflies were found to be more abundant in the river basin. In order of abundance, stonefly Tetropina, mayJlies Caenis, and centroptilum, and caddisJly Macrostemum were the most common geneva. The diversity of the EPTfauna ranged 1.41 - 2.65 with significantly different distribution (ANOVA, F/534o = 1.68) at P= 0.05 and fairly unevenly distributed (Evennes Index Ranged 0.15-0.95). The EPT Richness i~dices were in low ranges in all river and the FBI scores categorised the water quality of river in this river basin as moderately polluted to excellent.